INNOVATION TRAINING ACCOUNTING INDUSTRY MEET THE REQUIREMENTS OF INDUSTRIAL REVOLUTION 4.0 - Do Thi Thuy; Tran Thi Lan Anh; Bui Thi Minh (Journal of Applied Science and Technology, 2019)
Changing teaching methods, accounting training to match the development of the industrial revolution 4.0 and the development of the knowledge economy in the current trend of integration. On that basis, the paper proposes a number of recommendations to innovate the accounting profession to meet the requirements of the industrial revolution 4.0.